Health information-seeking behavior in stroke patients and its relationship with Behavioral decision-making: a latent profile analysis - Zhao, Ze-run; Yang, Meng; Feng, Juan-juan; Lan, Yu-meng; Zhong, Juan-ping; Li, Wei-ping; Wang, Xing-lei; Dou, Xin-man (Frontiers in Neurology, 2025)
ObjectiveThis study explored latent profiles of Health Information-Seeking Behavior (HISB) among stroke patients and analyzed its influencing factors.MethodsIn this cross-sectional study, 311 stroke participants from two tertiary care hospitals in Gansu Province, China, were recruited between January and May 2025 using convenience sampling. Data were collected using a general information questionnaire, the Health Information-Seeking Behavior Scale, and the Health Behavior Decision-Making Assessment Scale for Stroke Patients. Latent profile analysis (LPA) was employed to identify distinct HISB profiles.ResultsThree latent profiles were identified: the high-demand low-barrier positive group, the moderate-balanced group, and the low-demand high-barrier negative group. Key predictors of profile membership included age, education level, monthly personal income, and the presence of comorbid chronic diseases.ConclusionThe identification of three distinct HISB trait types provides an evidence-based foundation for developing personalized health education and tailored decision support interventions. Healthcare professionals can leverage this classification system to customize communication strategies for patients with different traits, deliver tiered information support, and ultimately empower patients to achieve better health behaviors and health outcomes.